1867 By-Laws of the University of South Carolina, Regulations of the Faculty, at 35-37, § 6 (W. W. Deane). - (:unkn) unknown (General Publisher, 1867)
Students are strictly forbidden to visit bar-rooms, grog-shops, or disorderly houses; or to use, or bring within the precincts of the University, any intoxicating liquors; or to have about their persons, or keep in their rooms, any deadly weapon, which may be secretly carried: upon pain of admonition, suspension, or report for expulsion, at the discretion of the Faculty. Any student who shall be guilty of any atrocious or infamous offence, who shall fight a duel, or give or accept a challenge to fight a duel, or who shall carry any challenge to fight a duel, or act as a second to those who shall give or accept a challenge, shall be forthwith suspended from the University, and reported for expulsion.”
--
Keywords: POSSESSION; DUELING